2005
DOI: 10.1111/j.1539-6924.2005.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Invasive Species in the Great Lakes Versus Their Eurasian Source Populations: Insights for Risk Analysis

Abstract: Combining DNA variation data and risk assessment procedures offers important diagnostic and monitoring tools for evaluating the relative success of exotic species invasions. Risk assessment may allow us to understand how the numbers of founding individuals, genetic variants, population sources, and introduction events affect successful establishment and spread. This is particularly important in habitats that are "hotbeds" for invasive species--such as the North American Great Lakes. This study compares genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
136
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 35 publications
9
136
0
1
Order By: Relevance
“…If the high neutral genetic diversity corresponds to adaptive genetic variation in coding loci, then the expansion of D. rostriformis bugensis may be coupled to enhanced adaptability (Zayed and Whitfield 2008). Similar large-scale introductions, high genetic diversity and no founder effects have been found for D. rostriformis bugensis and D. polymorpha in the Great Lakes (Hebert et al 1989;Marsden et al 1995;Stepien et al 2002Stepien et al , 2005 and in Ireland (Astanei et al 2005) and have been reported for Ponto-Caspian invasive fish species in North America (Stepien et al 1998(Stepien et al , 2005Stepien and Tumeo 2006;Brown and Stepien 2009).…”
Section: Discussionmentioning
confidence: 89%
“…If the high neutral genetic diversity corresponds to adaptive genetic variation in coding loci, then the expansion of D. rostriformis bugensis may be coupled to enhanced adaptability (Zayed and Whitfield 2008). Similar large-scale introductions, high genetic diversity and no founder effects have been found for D. rostriformis bugensis and D. polymorpha in the Great Lakes (Hebert et al 1989;Marsden et al 1995;Stepien et al 2002Stepien et al , 2005 and in Ireland (Astanei et al 2005) and have been reported for Ponto-Caspian invasive fish species in North America (Stepien et al 1998(Stepien et al , 2005Stepien and Tumeo 2006;Brown and Stepien 2009).…”
Section: Discussionmentioning
confidence: 89%
“…Ruffe, a percid fish native to western and northern Europe, was first observed in North America in the St. Louis River (the westernmost tributary of Lake Superior) in 1986 (Pratt 1988), having likely been introduced via ballast water of vessel(s) originating from a port associated with the Elbe River drainage (Stepien et al 2005). A rapidly reproducing population of Ruffe in the St. Louis River, combined with declines in some native fish populations and a persistent eastward advance, led the Aquatic Nuisance Species Task Force, under the authority of the Nonindigenous Aquatic Nuisance Prevention and Control Act, to declare Ruffe a 'nuisance species' in the spring of 1992.…”
Section: Introductionmentioning
confidence: 99%
“…While many recent studies have described the distribution of tubenose goby (Naseka et al, 2005;Hayden and Miner, 2009;Szaloky et al, 2015), its genetic diversity (Dillon and Stepien, 2001;Stepien et al, 2005) and their parasites (Kvach and Oguz, 2009;Huyse et al, 2015;Kvach et al, 2016), little or no information is presently available on the species' relationship with native fish species and its role in the food chain (but see Mikl et al, 2017). The European perch (Perca fluviatilis) is one of the most common fish predators in European waters, and certainly along the rip-rap banks of the Musov reservoir (AdĂĄmek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%